2020
DOI: 10.48550/arxiv.2008.03213
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

6G Wireless Systems: Vision, Requirements, Challenges, Insights, and Opportunities

Abstract: Mobile communications have been undergoing a generational change every ten years or so. However, the time difference between the so-called "G's" is also decreasing. While fifth-generation (5G) systems are becoming a commercial reality, there is already significant interest in systems beyond 5G -which we refer to as the sixth-generation (6G) of wireless systems. In contrast to the many published papers on the topic, we take a top-down approach to 6G. More precisely, we present a holistic discussion of 6G system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 203 publications
(304 reference statements)
0
19
0
Order By: Relevance
“…The authors in [6] have shown that even with an infinite number of antennas, a residual interference remains at the output of any of the above combiners. It has been also noted that for a large number of antennas, all the above combiners converge to 1 N H m , [34]. Accordingly, the equivalent channel impulse response between the transmitted symbols at subcarrier m ′ of terminal k ′ and the received and combined signal at subcarrier m of BS output corresponding to terminal k may be expressed as…”
Section: Massive Mimo Fbmc: Asymptotic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in [6] have shown that even with an infinite number of antennas, a residual interference remains at the output of any of the above combiners. It has been also noted that for a large number of antennas, all the above combiners converge to 1 N H m , [34]. Accordingly, the equivalent channel impulse response between the transmitted symbols at subcarrier m ′ of terminal k ′ and the received and combined signal at subcarrier m of BS output corresponding to terminal k may be expressed as…”
Section: Massive Mimo Fbmc: Asymptotic Analysismentioning
confidence: 99%
“…To summarize, the main contributions of this paper are the following; (1) We propose a joint multiuser and spectrally efficient channel estimation technique for the uplink of FBMCbased networks that is applicable to massive MIMO with both co-located and distributed antennas. We also derive the required statistics of the channel estimation errors to be used for their compensation at the equalization stage; (2) We investigate the channel equalization problem in FBMC-based massive MIMO and propose a practical two-stage equalization tech-nique that is highly effective in both co-located and distributed antenna architectures; (3) We take into account the equalizer length in the design procedure to achieve an equalizer with a practical length; (4) We integrate the PDP estimates of the channel into our equalizer design framework and propose a practical PDP-based equalizer with a practical/short length; (5) We formulate FBMC-based cell-free massive MIMO for the first time and investigate channel estimation and equalization in this setup; (6) We derive the statistical characteristics of the estimation errors of our proposed channel estimator and incorporate them into our proposed equalizers to tackle the imperfect CSI effects.…”
mentioning
confidence: 99%
“…Fourth, ubiquitous access through these systems necessitates the use of edge computing and storage. Nonetheless, computing problems will arise due to the onboard limitations of small satellites [88]. Thus, it necessary to develop novel networking frameworks that overcome the computing limitations and provide low latency THz communications for NTNs.…”
Section: Ntnsmentioning
confidence: 99%
“…Existing wireless networks, such as the sub 6 GHz, suffers from a severe bandwidth shortage which is even exacerbated with the explosive increase in the user devices [6]. Fortunately, the mmWave and the emerging THz bands can considerably overcome this shortcoming by providing an extra 3.25 GHz and 10-100 GHz bandwidth, respectively [38]. It is also expected that modern wireless user devices will be equipped with advanced capabilities that enable them to aggregate all these three frequency bands, i.e., the sub 6GHz, mmWave, and THz, to support future disruptive technologies and services [39].…”
Section: A Radio Resources: Definitions and Types (Or Issues)mentioning
confidence: 99%